2019
DOI: 10.1002/jcb.28602
|View full text |Cite
|
Sign up to set email alerts
|

Arctigenin improves lipid metabolism by regulating AMP‐activated protein kinase and downstream signaling pathways

Abstract: Although it has been reported that arctigenin (ARG) can reduce the body weight and inhibit adipogenic differentiation by activating AMP-activated protein kinase (AMPK), the exact signals responsible for the ARG-mediated antiobesity mechanism through AMPK are not well understood. In this study, we investigated the potential improvement of AGR on lipid metabolism using a high-fat diet (HFD)-induced hyperlipidemia rats and 3T3-L1 mature adipocytes.The levels of AMPK and its downstream factors were examined by Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…34 The adipocytedifferentiation markers include PPARγ, PPARα, and C/EBPα, and the genes related to lipid metabolism include LPL, AP2, sterol regulatory element binding protein (SREBP) 1 c, FAS, acetyl-CoA carboxylate 1 (ACC1) and carnitine palmitoyltransferase 1B (CPT1B). 35 PPARγ and C/EBPα play synergistic roles in the activation and expression of genes that are activated in differentiation, and participate in a major adipocyte change. 36 In the present study, HFD rats exposed to irradiation showed a significant increase in body weight, accompanied by immense visceral adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…34 The adipocytedifferentiation markers include PPARγ, PPARα, and C/EBPα, and the genes related to lipid metabolism include LPL, AP2, sterol regulatory element binding protein (SREBP) 1 c, FAS, acetyl-CoA carboxylate 1 (ACC1) and carnitine palmitoyltransferase 1B (CPT1B). 35 PPARγ and C/EBPα play synergistic roles in the activation and expression of genes that are activated in differentiation, and participate in a major adipocyte change. 36 In the present study, HFD rats exposed to irradiation showed a significant increase in body weight, accompanied by immense visceral adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK plays an important role in regulating the energy balance of cells. Activation of AMPK increases glucose uptake and FAO in metabolic diseases such as diabetes [ 45 , 46 ]. LKB1 is the main regulator of AMPK activation, and it can directly phosphorylate AMPK Thr-172 and activate its enzyme activity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…SREBP-1C is a crucial transcription factor, which binds to the endoplasmic reticulum to regulate triglyceride and fatty acid synthesis (26). Moreover, SREBP-1C is involved in de novo fatty acid synthesis via regulating the expression of ACC (27). Previous research indicated that decreasing the expression of SREBP-1C results in a decline of the incidence of dyslipidemia and simultaneously suppresses ACC expression in C57BL/6J mice (28).…”
Section: Discussionmentioning
confidence: 99%